Clinical Outcome of Home Hemodialysis in Patients with Previous Peritoneal Dialysis Exposure: Evaluation of the Integrated Home Dialysis Model. Issue 3 (May 2015) - Nadeau-Fredette, Annie-Claire; Bargman, Joanne M.; Chan, Christopher T.
Background: Home dialysis is a cost-effective modality of renal replacement therapy associated with excellent outcomes. Peritoneal dialysis (PD) is the most common home-based modality, but technique failure remains a problem. Transfer from PD to home hemodialysis (HHD) allows the patient to continue with a home-based modality, but the outcomes of patients transitioning to HHD after PD are largely unknown. Methods: In a retrospective cohort study, including all consecutive HHD patients between January 1996 and December 2011, we evaluated the outcomes of patients with previous PD exposure compared to those without. The primary outcome was the cumulative patient and technique survival. Secondary outcomes included time to first hospitalization and hospitalization rate. Data were compared using the log-rank test and a multivariable Cox proportional hazards model. Results: Among our cohort of 207 consecutive HHD patients, 35 (17%) had previous exposure to PD. Median renal replacement therapy (RRT) vintage (12.3 years, interquartile range (IQR) 8.5 – 18.9 vs 0.9 years, IQR 0.2 – 7.5, p < 0.001) and Charlson comorbidity index (CCI) (4, IQR 2 – 6 vs 3, IQR 2 – 4, p = 0.044) were higher among patients with PD exposure than those without. Despite the difference in vintage, cumulative patient and technique survival was similar in the two groups, in both unadjusted (log-rank p = 0.893) and Cox adjusted models (hazard ratio (HR) 1.15, 95% confidence interval (CI) 0.51 – 2.59) for patients with PD exposure compared to those without. The time to first hospitalization was shorter in patients with previous PD exposure compared to PD-naïve patients (log-rank p = 0.021). This association was preserved in the Cox proportional model (HR 1.65, 95% CI 1.08 – 2.54). Conclusion: Despite a higher burden of comorbidity, patients with previous PD exposure had similar cumulative patient and technique survival on HHD compared to those without PD exposure. Whenever possible, HHD should be considered in PD patients in need of a new dialysis modality.